LARVICIDAL ACTIVITY OF Caesalpinia ferrea MART. AND Lippia origanoides CHAM. AGAINST Aedes aegypti (LINNAEUS, 1762) (DIPTERA: CULICIDAE) - Andre Santos de Andrade, Thiago; Maria de Santana, Ivanise; Chaves Jimenez, George; Tereza Nery Farias, Eulina; Oliveira de Macedo, Lucia; Camara Alves, Leucio; Antonio Nascimento Ramos, Rafael; Aparecida da Gloria Faustino, Maria; Aparecida de Carvalho, Gilcia (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
The control of Aedes aegypti has been considered one of the most important public health challenges worldwide. Chemical compounds have long been used for this purpose, but resistance to these molecules has also increased. Therefore, over the last few years several studies have focused on the development of alternative tools, particularly those based on plant metabolites. The purpose of this study was to assess the larvicidal activity of Caesalpinia ferrea and Lippia origanoides against Ae. aegypti. Larvae (L3) of Ae. aegypti Liverpool and Rockefeller strains, as well as of the Recife population were exposed to different concentrations of C. ferrea (ranging from 13.1 to 105 mg/mL) and L. origanoides (ranging from 16.3 to 130 mg/mL), and the mortality rate was evaluated up to 48 hours after the beginning of the experiment. All tested groups and ontrol group were quadruplicated. For C. ferrea, mortality ranged from 42.5% to 100% for Ae. aegypti Liverpool strain, from 67% to 100% for Ae. aegypti Rockfeller strain, and 57% to 100% for Ae. aegypti Recife population after 48 hours of larval exposure. For L. origanoides, the larvicidal activity ranged from 75% to 100% for Ae. aegypti Liverpool strain, from 61.5% to 100% for Ae. aegypti Rockfeller strain, and from 60.5% to 100% for Ae. aegypti Recife population. The hydro ethanol extract of C. ferrea and L. origanoides presented larvicidal activity against Ae. aegypti. KEY WORDS: Aedes aegypti; hydro ethanol extracts; Caesalpinia ferrea; Lippia sidoides; botanical insecticide; mosquitoes.